Systematic Literature Review: The Effect of Quality of Work-Life Balance and Corporate Culture on Employee Engagement - Akhirudin Akhirudin; Bambang Moertono Setiawan; Nur Wening; Sujoko Sujoko (Interdiciplinary Journal and Hummanity (INJURITY), 2024)
This study explores the impact of work-life balance and organizational culture on employee engagement within an organization. As companies navigate the global market, human resources play a critical role in determining performance and competitive advantage. Organizational culture serves as a guiding framework that shapes employee behavior, while work-life balance directly influences employee well-being and productivity. Using a Systematic Literature Review (SLR) methodology, the study synthesizes findings from peer-reviewed publications indexed in Sinta, focusing on the relationships between these variables. The results indicate that both work-life balance and organizational culture significantly contribute to higher levels of employee engagement, enhancing motivation, commitment, and organizational performance. Employees in environments that prioritize work-life balance and foster open, participatory cultures tend to be more productive and loyal, reducing turnover rates. This research highlights the importance of creating policies that support a healthy work-life balance and positive work culture to improve employee engagement. Future research could examine these variables longitudinally, consider industry-specific dynamics, and incorporate qualitative methods for deeper insights.